Feedback activation of neurofibromin terminates growth factor-induced Ras activation. Issue 1 (December 2016) - Hennig, Anne; Markwart, Robby; Wolff, Katharina; Schubert, Katja; Cui, Yan; Prior, Ian; Esparza-Franco, Manuel; Ladds, Graham; Rubio, Ignacio
Abstract Background Growth factors induce a characteristically short-lived Ras activation in cells emerging from quiescence. Extensive work has shown that transient as opposed to sustained Ras activation is critical for the induction of mitogenic programs. Mitogen-induced accumulation of active Ras-GTP results from increased nucleotide exchange driven by the nucleotide exchange factor Sos. In contrast, the mechanism accounting for signal termination and prompt restoration of basal Ras-GTP levels is unclear, but has been inferred to involve feedback inhibition of Sos. Remarkably, how GTP-hydrolase activating proteins (GAPs) participate in controlling the rise and fall of Ras-GTP levels is unknown. Results Monitoring nucleotide exchange of Ras in permeabilized cells we find, unexpectedly, that the decline of growth factor-induced Ras-GTP levels proceeds in the presence of unabated high nucleotide exchange, pointing to GAP activation as a major mechanism of signal termination. Experiments with non-hydrolysable GTP analogues and mathematical modeling confirmed and rationalized the presence of high GAP activity as Ras-GTP levels decline in a background of high nucleotide exchange. Using pharmacological and genetic approaches we document a raised activity of the neurofibromatosis type I tumor suppressor Ras-GAP neurofibromin and an involvement of Rsk1 and Rsk2 in the down-regulation of Ras-GTP levels. Conclusions Our findings show that, in addition to feedback inhibition of Sos, feedback stimulation of the RasGAP neurofibromin enforces termination of the Ras signal in the context of growth-factor signaling. These findings ascribe a precise role to neurofibromin in growth factor-dependent control of Ras activity and illustrate how, by engaging Ras-GAP activity, mitogen-challenged cells play safe to ensure a timely termination of the Ras signal irrespectively of the reigning rate of nucleotide exchange.